Mapping the Global ICT Research Trends in the Construction Sector - Emere, Chijioke Emmanuel; Oguntona, Olusegun Aanuoluwapo (Journal of Information System and Informatics, 2025)
Information and communication technology (ICT) has not been widely adopted in the construction sector, despite its promise to improve productivity, safety, communication, efficiency, and sustainability. Prior research has made clear that further research and development in this field are required to improve its application for project delivery and organisational performance, particularly in developing countries. To determine the area of focus of earlier studies, this paper reviewed ICT in fields relevant to construction. Utilising a bibliometric methodology, the data for this study were taken from the Scopus database. Keyword searches were used to search the database, such as “Information communication technology/technologies”, “Information communication”, “Communication technology”, and “Construction or Construction industry”, to obtain pertinent papers. The papers analysed were 96 in number from 2014-2024. Using VOSviewer, a network and overlay visualisation map of the co-occurrence keywords was produced based on the gathered bibliographic data. The findings indicated that earlier research in ICT gave priority to information and data management, project design, sustainable project management, power transmission and smart grids, construction project communication, and safety management and training. Furthermore, research in this area is currently concentrating on big data applications, smart city applications, and sustainable development applications. The results highlight a knowledge vacuum in which South American and African nations might investigate to enhance construction project delivery and organisational performance. This work adds to the conversation around ICT, which has not gotten much attention in recent scientometric and bibliometric research.